Proteinuria in Kidney Transplant Recipients (Bangladesh Journal of Urology, 2020)
Objectives: Proteinurea is one of the major causes of early graft rejection and high degree mortality in renal transplant patients. Our objective was to assess risk in post transplant patient for proteinurea and it’s appropriate management.Methods: This cross sectional study includes fifty adult kidney allograft recipients, transplanted in kidney transplant unit of Urology Department, Bangabandhu Sheikh Mujib Medical University in the period of January 2012 to December 2012.Results: In our series, proteinuria was detected in 44% of the renal transplant recipients in variant amount. In this study the male and female ratio was 7:3. There was a highly significant level of proteinuria in proteinuric group than that of non-proteinuric group [538.09 (313.36) mg/24 hr vs. 44.48 (23.39) mg/24 hr; p value